THE INFLUENCE OF WORKLOAD, WORK ETHICS, AND AFFECTIVE COMMITMENT ON EMPLOYEE PERFORMANCE AT APOTEK SEMESTA GROUP - Febriyanti, Rani; Trias Setyowati; Septy Holisa Umamy (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the impact of workload, work ethics, and affective commitment on employee performance at Apotek Semesta Group. The primary focus of this research is to identify the factors influencing employee performance and provide recommendations for better human resource management. Method: A quantitative approach was employed using regression analysis to examine the relationship between the independent variables (workload, work ethics, and affective commitment) and the dependent variable (employee performance). Apotek Semesta Group was selected as the research site due to its diverse work environment and high relevance to the research topic. Data was collected through surveys from employees and analyzed using SPSS 20 software. Results: The results indicate that workload significantly affects employee performance, with a t-statistic of 2.532, which is greater than the t-table value of 2.00100, and a significance level of 0.000, which is less than 0.05. Work ethics also significantly influences performance, with a t-statistic of 2.784, greater than the t-table value of 2.00100, and a significance level of 0.001, which is less than 0.05. Furthermore, affective commitment was found to have a significant contribution to employee performance, with a t-statistic of 3.024, greater than the t-table value of 2.00100, and a significance level of 0.004, which is less than 0.05. Novelty: The conclusion of this study is that workload, work ethics, and affective commitment significantly impact employee performance. Therefore, companies are encouraged to consider these factors to improve employee performance and work effectiveness, and to develop more optimal human resource management strategies.